2020
DOI: 10.1177/0049475519896942
|View full text |Cite
|
Sign up to set email alerts
|

The role of pyridostigmine in recovery from motor paralysis in a snakebite patient with an allergic reaction to anti-snake venom

Abstract: A 30-year-old woman presented as an emergency with a history of snakebite 5 h previously with signs of bulbar palsy, ptosis, respiratory distress and weakness of all four limbs. Mechanical ventilation, anti-snake venom (ASV) and supportive management were immediately instituted. With the third dose of ASV, an early anaphylactic reaction ensued. Subsequent management with corticosteroids and antihistamines over the next few days allowed consciousness to return but muscle power did not improve beyond 2/5. A tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Sung and Hah 7 reported a case of extraocular muscle paresis following a snakebite. It was reported that a patient, supported with a mechanical ventilator due to the neuromuscular paralysis, which was developed about 5 hours after snakebite, was resuscitated successfully using intravenous neostigmine and oral pyridostigmine 8 . In our patient, symptoms developed at the tenth hours, and after treatment, the symptoms improved fastly similar to the other cases in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Sung and Hah 7 reported a case of extraocular muscle paresis following a snakebite. It was reported that a patient, supported with a mechanical ventilator due to the neuromuscular paralysis, which was developed about 5 hours after snakebite, was resuscitated successfully using intravenous neostigmine and oral pyridostigmine 8 . In our patient, symptoms developed at the tenth hours, and after treatment, the symptoms improved fastly similar to the other cases in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pyridostigmine (Mestinon, Korean Drug, Seoul, South Korea) 180 mg per day (60 mg tablet three times daily) and VVse (Entelon, Hanlim Pharm, Seoul, South Korea) 300 mg per day (150 mg tablet twice daily) were administered to relieve the neurological symptoms and improve arm swelling, respectively. 7,8 The symptoms significantly improved on the third day following the snakebite. On the fifth day, the right arm swelling recovered to near normal, and the laboratory test results revealed no unusual findings (Table 1).…”
Section: Casementioning
confidence: 97%
“…A skin allergy test for antivenom administration was positive, and the patient was deemed unsuitable for antivenom administration. Therefore, pyridostigmine (Mestinon, Korean Drug) 180 mg/day (60 mg tablet three times daily) and VVse (Entelon) 300 mg/day (150 mg tablet twice daily) were administered to relieve the neurological symptoms and improve arm swelling, respectively [ 7 , 8 ]. The symptoms significantly improved on the third day following the snakebite.…”
mentioning
confidence: 99%